Effect of Digested Selected Food Items on Markers of Oxidative Stress and Inflammation in a Caco-2-Based Human Gut Epithelial Model - Farhad Vahid; Pit Krischler; Bernadette Leners; Torsten Bohn (MDPI AG, 2024)
The human gut epithelium presents a crucial interface between ingested food items and the host. Understanding how different food items influence oxidative stress and inflammation in the gut is of great importance. This study assessed the impact of various digested food items on oxidative stress, inflammation, and DNA/RNA damage in human gut epithelial cells. Differentiated Caco-2 cells were exposed to food items and their combinations (n = 22) selected from a previous study, including sausage, white chocolate, soda, coffee, orange juice, and curcumin. Following stimulation with TNF-α/IFN-1β/LPS and H2O2 for 4 h, the cells were exposed to digested food items or appropriate controls (empty digesta and medium) for a further 16 h. Cell viability, antioxidant capacity (ABTS, FRAP), IL-6, IL-8, F2-isoprostanes, lipid peroxidation (MDA), and DNA/RNA oxidative damage were assessed (3 independent triplicates). The ABTS assay revealed that cells treated with "white chocolate" and "sausage + coffee" exhibited significantly reduced antioxidant capacity compared to stimulated control cells (ABTS = 52.3%, 54.8%, respectively, p < 0.05). Similar results were observed for FRAP (sausage = 34.9%; white chocolate + sausage = 35.1%). IL-6 levels increased in cells treated with "white chocolate + sausage" digesta (by 101%, p < 0.05). Moreover, MDA levels were significantly elevated in cells treated with digested "sausage" or sausage in combination with other food items. DNA/RNA oxidative damage was found to be higher in digesta containing sausage or white chocolate (up to 550%, p < 0.05) compared to stimulated control cells. This investigation provides insights into how different food items may affect gut health and underscores the complex interplay between food components and the epithelium at this critical interface of absorption.